2021
DOI: 10.3390/nu13114130
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Diet Quality in a Sample of Rural and Urban Australian Adults

Abstract: The diet quality of rural Australians is under researched. Characterising disparities in diet quality between rural and urban populations may inform targeted interventions in at- risk groups. A cross-sectional study aimed to determine the relationship between diet quality, rurality and sociodemographic characteristics in a sample of Australian adults. Participants were recruited at rural and regional events between 2017 and 2020, in New South Wales, Australia. Diet quality was measured using the Healthy Eating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…This equates to a diet quality categorized as ‘getting there’. In our previously reported comparison of diet quality with CHAaRGE:20 participants of other age groups, those aged over 71 years had higher scores for diet quality compared to 18–30-year-old participants [ 30 ]. Several risk factors that relate to lower diet quality were reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This equates to a diet quality categorized as ‘getting there’. In our previously reported comparison of diet quality with CHAaRGE:20 participants of other age groups, those aged over 71 years had higher scores for diet quality compared to 18–30-year-old participants [ 30 ]. Several risk factors that relate to lower diet quality were reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors that relate to lower diet quality were reported here. For example, previous research has shown that living alone is one such risk factor [ 30 , 33 ]. Approximately one third of this sample lived alone, and is consistent with other populations [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, participants who indicated that they consume fat-based spreads showed higher odds of obesity. Previous reports have linked excess caloric intake to chronic diseases [ 15 , 31 ]. In one study, overconsumption of fats increased the risk of obesity, coronary heart disease, diabetes, and cancer [ 31 ] and in another, a better quality diet resulted in better quality of life and greater emotional wellbeing, especially among women [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key outcome variable in the study was obesity prevalence in surveyed towns (as calculated from weight and height measured at the clinic), which was categorized in binary form as a “Yes” (1 = if the participant had obesity [ 1 , 8 , 14 ]) and otherwise “No” (0). Previous studies on obesity prevalence, especially from rural areas [ 7 , 8 , 15 , 16 , 17 ], played a role in the exploratory variables selected for the study based on the data available in the pooled dataset. These variables were grouped into five classes: The demographic level factors included age group, gender, ethnicity (Australia born versus non-Australia born) and place of residence (rural or regional).…”
Section: Methodsmentioning
confidence: 99%